Chimeric Antigen Receptor (CAR) Immunotherapy for Natural Killer (NK) cells, therapeutic approaches and future perspectives in the oncological field: a systematic review of Synthesis Without Meta-analysis (SWIM) (Research, Society and Development, 2025)
CAR-T cell immunotherapy, despite its success in hematological malignancies, is limited by significant toxicities and high production costs. CAR-NK immunotherapy emerges as an alternative, with the potential for safer and more accessible "off-the-shelf" allogeneic products. The objective was to critically analyze the evidence on the production, efficacy, challenges, and future perspectives of CAR-NK immunotherapy. A systematic review was conducted using the SWIM (Synthesis Without Meta-analysis) protocol, with the analysis of 83 documents (after applying inclusion and exclusion criteria) analyzed via Bardin's Content Analysis. High efficacy was demonstrated in hematological malignancies, but limited success in solid tumors due to low persistence and suppression by the Tumor Microenvironment (TME). The strategic transition to Induced Pluripotent Stem Cells (iPSCs) is the foundation for producing universal CAR-NK immunotherapies. Overcoming barriers in solid tumors depends on the engineering of multifunctional "armored" CAR-NK cells. This includes the development of "NK-centric" constructs (such as the NKG2D domain), the co-expression of supportive Interleukins (IL-15/IL-21) to increase persistence, and gene editing (via CRISPR-Cas9) to resist TME suppression and metabolic stress (e.g., DRP1 ablation). The integration of these advanced strategies into iPSC platforms is fundamental to consolidating CAR-NK therapy as an accessible and effective pillar in the treatment of cancer and autoimmune diseases. For this, conducting more robust studies is of utmost importance in order to improve the scientific evidence regarding this therapy.